Age and training-related changes on body composition and fitness in male amateur cyclists - Alvero-Cruz, José Ramón; García-Romero, Jerónimo; Ordoñez, Francisco Javier; Mongin, Denis; Correas-Gómez, Lorena; Nikolaidis, Pantelis T.; Knetchle, Beat (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Master athletes are considered as a model of healthy aging because they can limit the age-related decline of physiological abilities compared to sedentary individuals. The main objective of this study is to analyze age-related changes and annual training on body composition (BC) and cardiorespiratory fitness (CRF) parameters. The participants in this retrospective cross-sectional study were 176 male cyclists, aged 40–60 years. BC was evaluated through anthropometric measurements and CRF was determined by an incremental cycle ergometer test to exhaustion. A comparative study between age groups was carried out through a one-way ANOVA test and the associations between the variables were assessed by Spearman’s correlation coefficients and multiple regression analysis to estimate the performance. Training was generally associated with a decrease in both body weight and body fat (p < 0.05). A decrease in resting heart rate was observed as a vagal effect of kilometers cycled per year (p < 0.05). Kilometers cycled per year were associated with an increase in peak power output, which was larger in the master 40 group (p < 0.05) with a non-significant upward in VO2 max (p > 0.05). In the performance prediction model, the included variables explained 52% of the variance. In summary, the changes induced by age were minimal in BC and negligible in CRF, whereas HR decreased with age. Training load was generally associated with a decrease in body weight, BMI and body fat percentage that was particularly notable in the abdominal skin folds. A decrease in HRrest was observed as a vagal effect due to kilometers cycled per year, and age did not seem to have a significant effect. The annual cycling kilometers were associated with to high PPO that is greater in the M40 group and a non-significant upward trend in VO2 max. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Ejercicio físico - Aspectos fisiológicos; Body Composition; Body Mass Index; Cardiorespiratory Fitness; Cross-Sectional Studies; Exercise; Humans; Male; Oxygen Consumption; Retrospective Studies